Punjabi (Lyallpuri variety). (5th August 2020) - Hussain, Qandeel; Proctor, Michael; Harvey, Mark; Demuth, Katherine
Abstract : Punjabi (Western, ISO-639-3 pnb) is an Indo-Aryan language (Indo-European, Indo-Iranian) spoken in Pakistan and India, and in immigrant communities in the UK, Canada, USA, and elsewhere. In terms of number of native speakers, it is ranked 10th among the world's languages, with more than 100 million speakers (Lewis, Simons & Fennig 2016). Aspects of the phonology of different varieties of Punjabi have been described in Jain (1934), Arun (1961), Gill & Gleason (1962), Singh (1971), Dulai & Koul (1980), Bhatia (1993), Malik (1995), Shackle (2003), and Dhillon (2010). Much of this literature is focused on Eastern varieties, and the phonology of Western Punjabi dialects has received relatively less attention (e.g. Bahri 1962, Baart 2003, 2014).